A Rare Case of Metaplastic Breast Carcinoma with Squamous Differentiation in Young Female: A Case Report - Agustina, Rohana (Sanus Medical Journal, 2022)
Background. Metaplastic breast carcinoma is a very rare breast cancer, only about 0.2"‘1% of all invasive breast carcinomas. The prognosis of these cancer is poor and aggressive, reported to have lower response rates to conventional adjuvant chemotherapy and a worse clinical outcome after chemotherapy than other forms triple"‘negative breast carcinomas. Histopathologically, metaplastic breast carcinoma has distinct patterns with different outcomes. Among the types of metaplastic carcinoma, squamous cell, high grade spindle cell and high grade adenosquamous carcinoma are associated with the worst prognosis. We report one case of metaplastic breast carcinoma with squamous differentiation in young patient. Methods. We examined the breast tumor tissue of a female patient, evaluated the macroscopic and microscopic features and asked the patient about the clinical course of the disease. Inform consent was obtained from the patient for publication of this case report and accompanying images. Results. We reported a young female patient with final diagnosis of pathology Mixed Infiltrating Duct Carcinoma of No Special Type Grade 3 and Metaplastic Breast Carcinoma with Squamous Differentiation (30%) that has invaded fat tissue with Ductal Carcinoma Insitu of High Nuclear Grade 3 with basis of the operation is still positive for the tumor mass. Patients lost follow"‘up and did not continue therapy. Conclusion. Morphology of metaplastic breast carcinoma are important factors influencing patient outcome. Early diagnosis and wide local excision of the squamous"‘type metaplastic breast carcinoma mass can make a better prognosis.